Diseñamos un circuito eléctrico - Ramirez Atoche, Marleni (2018)
The purpose of the present work of Professional Sufficiency, is to develop my learning session, called "We design an electrical circuit" directed to the students of fourth grade students of Primary Education at “Santa Rosa de Lima” Parochial School in Talara city, Piura Region. The work of Professional Sufficiency, consists to design a Learning Session, in the Science and Environment area, with the purpose of developing in the students the competence: Design and produce technological prototypes; through a demonstrative class, deploying a series of strategies of Teaching and Learning, in the same way making use of means and concrete educational materials, so that the students have the facility of developing and increasing their knowledge in the area in mention, so that later they can put in practice this knowledge, when solving multiple problematic situations of their daily life. In the development of the learning session, all the facilities and corresponding support are provided, so that the students have full confidence and autonomy in the acquisition of new knowledge, so that, at the end of the class, the students are able to apply all that they have learned, solving a work sheet.